Association between gut microbiota and bone metabolism: Insights from bibliometric analysis - Zhang, Zhanrong; Zhang, Zheng; Shu, Haoming; Meng, Yichen; Lin, Tao; Ma, Jun; Zhao, Jianquan; Zhou, Xuhui (Frontiers in Physiology, 2023)
Gut microbiota has been reported to participate in bone metabolism. However, no article has quantitatively and qualitatively analyzed this crossing field. The present study aims to analyze the current international research trends and demonstrate possible hotspots in the recent decade through bibliometrics. We screened out 938 articles meeting the standards from 2001 to 2021 in the Web of Science Core Collection database. Bibliometric analyses were performed and visualized using Excel, Citespace, and VOSviewer. Generally, the annual number of published literatures in this field shows an escalating trend. The United States has the largest number of publications, accounting for 30.4% of the total. Michigan State University and Sichuan University have the largest number of publications, while Michigan State University has the highest average number of citations at 60.00. Nutrients published 49 articles, ranking first, while the Journal of Bone and Mineral Research had the highest average number of citations at 13.36. Narayanan Parameswaran from Michigan State University, Roberto Pacifici from Emory University, and Christopher Hernandez from Cornell University were the three professors who made the largest contribution to this field. Frequency analysis showed that inflammation (148), obesity (86), and probiotics (81) are keywords with the highest focus. Moreover, keywords cluster analysis and keywords burst analysis showed that “inflammation”, “obesity”, and “probiotics” were the most researched topics in the field of gut microbiota and bone metabolism. Scientific publications related to gut microbiota and bone metabolism have continuously risen from 2001 to 2021. The underlying mechanism has been widely studied in the past few years, and factors affecting the alterations of the gut microbiota, as well as probiotic treatment, are emerging as new research trends.